Environmental law case book - "Leelakrishnan, P." (New Delhi, 2004)
The development of science and technology gave rise to tremendous changes in the human environment. These changes upset the ecological system and the necessity to regulate human behaviour to suit and restore the ecological balance witnessed the emergence of a new branch of law, namely Environmental Law. In order to conform to the wider interpretation of environmental conditions namely, physical conditions of land, air and water, and the human environment namely health, social and other man made conditions which affect the environment, the book elucidates issues such as the different types of pollution and its hazards, forest habitat, judicial review, sustainable development and environmental process. This book is an asset to students as it explains the significant developments in environmental law in a clear and lucid style.
Keywords: Environmental law-Cases